Deux ou trois « choses » sur les noms généraux - Mathilde Salles (Corela)
The semantic poverty of general nouns and their referential versatility could make them excellent means to achieve a co-referential anaphora. Many contexts, however, do not allow a general noun like chose (‘thing’), personne (‘person’) or individu (‘individual’) to reiterate a previously classified referent. The difficulties of such reiterations or the (often pejorative) discursive effects they produce are linked to the referent declassification they involve. In fact, general nouns are distinguished from other superordinate nouns by their weak classifying power. This feature, instead, brings them closer to quality nouns (in Milner’s sense), which appear at the top of the generality continuum in some examples proposed by Halliday & Hasan.